Green-to-Red Photoconvertible Dronpa Mutant for Multimodal Super-resolution Fluorescence Microscopy - Moeyaert, Benjamien; Nguyen Bich, Ngan; De Zitter, Elke; Rocha, Susana; Clays, Koen; Mizuno, Hideaki; van Meervelt, Luc; Hofkens, Johan; Dedecker, Peter (ACS nano, 2014)
Advanced imaging techniques crucially depend on the labels used. In this work, we present the structure-guided design of a fluorescent protein that displays both reversibly photochromic and green-to-red photoconversion behavior. We first designed ffDronpa, a mutant of the photochromic fluorescent protein Dronpa that matures up to three times faster while retaining its interesting photochromic features. Using a combined evolutionary and structure-driven rational design strategy, we developed a green-to-red photoconvertible ffDronpa mutant, called pcDronpa, and explored different optimization strategies that resulted in its improved version, pcDronpa2. This fluorescent probe combines a high brightness with low photobleaching and photoblinking. We herein show that, despite its tetrameric nature, pcDronpa2 allows for multimodal subdiffraction imaging by sequentially imaging a given sample using both super-resolution fluctuation imaging and localization microscopy.